2013
DOI: 10.1016/j.surg.2013.05.013
|View full text |Cite
|
Sign up to set email alerts
|

Do giant parathyroid adenomas represent a distinct clinical entity?

Abstract: Background The size of abnormal parathyroid glands in patients with primary hyperparathyroidism is highly variable, but the clinical significance of giant glands is unknown. Methods 300 consecutive patients were reviewed following parathyroidectomy for primary hyperparathyroidism. We compared patients with giant parathyroid adenomas (weight ≥95th percentile) with the remaining patients. Results Giant adenomas were defined as weight ≥95th percentile or 3.5 grams (median 0.61 g, range 0.05–29.93). Patients w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(115 citation statements)
references
References 16 publications
6
105
0
4
Order By: Relevance
“…1 Pathological parathyroid glands, excised from patients with pHPT, show great variability in size and have a median estimated weight of 650mg. 3 The term 'giant parathyroid adenoma' is used in the literature to describe sporadic cases of parathyroid adenomas with a glandular mass greater than the median estimated. Various weight cut-offs have been used, the largest being 3.5g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Pathological parathyroid glands, excised from patients with pHPT, show great variability in size and have a median estimated weight of 650mg. 3 The term 'giant parathyroid adenoma' is used in the literature to describe sporadic cases of parathyroid adenomas with a glandular mass greater than the median estimated. Various weight cut-offs have been used, the largest being 3.5g.…”
Section: Discussionmentioning
confidence: 99%
“…3 Patients with giant parathyroid adenomas were more likely to have single gland disease as well as greater mean preoperative calcium and PTH levels compared with those with non-giant adenomas. No differences were recorded with regard to gland location, accuracy of imaging modalities, or persistent or recurrent pHPT.…”
Section: 3mentioning
confidence: 91%
See 1 more Smart Citation
“…Spanheimer et al 11 referred to giant adenomas as a distinct clinical entity. They tried to characterise the patients with giant parathyroid adenoma and compared them with other patients with pHPT; they concluded that ‘giant adenomas present with increased serum calcium and PTH levels and have higher rate of asymptomatic disease’.…”
Section: Discussionmentioning
confidence: 99%
“…Giant adenomas are defined as weighting ≥95th centile or ≥3.5 g11 and virtually all of them are PTH-secreting.…”
Section: Introductionmentioning
confidence: 99%